1996
DOI: 10.1161/01.cir.94.7.1647
|View full text |Cite
|
Sign up to set email alerts
|

Functional Upregulation of the Vascular Endothelial Growth Factor Receptor KDR by Hypoxia

Abstract: These data indicate that hypoxia stimulates VEGF-dependent signaling not only by upregulation of VEGF ligand but also by functional upregulation of a specific signaling receptor. Therefore, these data provide evidence that the endothelium plays an active role in hypoxia-induced angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
134
3
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 234 publications
(148 citation statements)
references
References 52 publications
9
134
3
2
Order By: Relevance
“…Gerber et al 34 showed that, in contrast to the flt-1 receptor, KDR is not induced by hypoxia. However, this finding contrasts to Waltenberger et al's 35 earlier report, where hypoxia upregulated the expression of KDR in the endothelial cells of umbilical veins. Upregulation of VEGF and KDR, which is paralleled by HIF1a expression, has also been recorded in rabbit skeletal muscle during acute hypoxia.…”
Section: Discussioncontrasting
confidence: 99%
“…Gerber et al 34 showed that, in contrast to the flt-1 receptor, KDR is not induced by hypoxia. However, this finding contrasts to Waltenberger et al's 35 earlier report, where hypoxia upregulated the expression of KDR in the endothelial cells of umbilical veins. Upregulation of VEGF and KDR, which is paralleled by HIF1a expression, has also been recorded in rabbit skeletal muscle during acute hypoxia.…”
Section: Discussioncontrasting
confidence: 99%
“…Although serum from animals with an acute myocardial infarct will stimulate proliferation of endothelial precursors, 25 our experimental model was devoid of ischemic organ injury and a serum-bound MSC transdifferentiation factor is unlikely. Since the VEGF gene is hypoxiaresponsive, 31 and we demonstrated de novo VEGF production by MSCs in vivo, we speculate that reduced oxygen tension milieu of Matrigel implant may provide the stimulus required to promote VEGF production by MSCs. We propose that VEGF production by MSCs occurs as part of an adaptive response to the relative hypoxia of the Matrigel milieu in vivo.…”
Section: Discussionmentioning
confidence: 74%
“…Studies of VEGFR2 expression in animal models of brain ischemia and in vitro models of neuronal or brain tissue hypoxia have yielded conflicting results. In some, VEGFR2 was upregulated [69][70][71][72][73] and in others, decreased [74][75][76]. Other factors that may account for the reduced or unchanged microvessel density in hyperperfused cortex in AD [3] include sequestration of VEGF by Aβ42 [55], the decreased VEGFR1:sVEGFR1 ratio (see above), and binding of Aβ42 to VEGFR2 -shown by Patel et al [2010] to block VEGF-mediated signaling.…”
Section: Discussionmentioning
confidence: 99%